Development and Validation of an Instrument to Measure Teachers’ Professional Agency during Curriculum Reform and Its Underlying Structure - Mohamed, Lawsha; Tunku Ahmad, Tunku Badariah (IIUM Press, 2018)
The purpose of this study was to develop and validate an effective instrument to measure teachers’ professional agency and its underlying factors. Of major concern was the appropriateness of the items and the underlying structure of teacher agency. One hundred and fourteen (N = 114) teachers from three primary schools in the Maldives filled out a teacher agency questionnaire. The validity and reliability of the instrument were tested using exploratory factor analysis and reliability analysis. Ninety-four items were developed in the initial item pool based on Priestley et al.'s (2015) ecological model of teachers’ professional agency. An exploratory factor analysis extracted nine factors from the 94-item instrument on teacher agency, which altogether explained 76.37% of the variance in the pattern of relationships among the items. All the nine factors had high reliabilities with Cronbach’s alphas greater than .791. Fifty-three items remained in the final questionnaire after deleting items with cross-loadings on multiple factors and loadings below .50. Hence, this study validated a nine-factor structure that represented the underlying dimensions of teachers' professional agency. This instrument could be used to gain a better understanding of the factors influencing teachers’ professional agency during a curriculum reform.